Working mothers' breastfeeding experience: a phenomenology qualitative approach - Rita Surianee Ahmad; Zaharah Sulaiman; Nik Hazlina Nik Hussain; Norhayati Mohd Noor (BMC, 2022)
Abstract Background Breastfeeding practice is influenced by the mother's attitude toward and knowledge of breastfeeding. Working mothers face many challenges and need support to maintain breastfeeding. This study aimed to explore working mothers' breastfeeding experiences and challenges that can influenced their practices. Methods The qualitative phenomenological approach involving working mothers in Kota Bharu who fulfilled the inclusion criteria and consented to participate in the study were recruited using purposive sampling. Sixteen participants aged 24 to 46 years were interviewed using semi-structured in-depth interviews in the study. All interviews were recorded in digital audio, transcribed verbatim and analyzed using thematic analysis. Findings Three main themes emerged from the data analysis: perception of breastfeeding, challenges in breastfeeding, and support for breastfeeding. Two subthemes for perceptions were perception towards breastfeeding and towards infant formula. Challenges had two subthemes too which were related to perceived insufficient milk and breastfeeding difficulty. Where else, two subthemes for support were internal support (spouse and family) and external support (friends, employer, and healthcare staff). Conclusions Maintaining breastfeeding after return to work is challenging for working mothers and majority of them need support to continue breastfeeding practice. Support from their spouses and families' influences working mothers' decision to breastfeed. Employers play a role in providing a support system and facilities in the workplace for mothers to express and store breast milk. Both internal and external support are essential for mothers to overcome challenges in order to achieve success in breastfeeding.